2013
DOI: 10.1063/1.4831661
|View full text |Cite
|
Sign up to set email alerts
|

Transport mechanisms and effective Schottky barrier height of ZnO/a-Si:H and ZnO/μc-Si:H heterojunction solar cells

Abstract: The impact of boron doping on the p-layer of thin film silicon solar cells is assessed by measuring the effective Schottky barrier height of ZnO/a-Si:H and ZnO/μc-Si:H heterojunctions. A deviation from ideal diode characteristics is revealed by an increase of ideality factor with doping concentration. Higher current densities and lower effective Schottky barriers are evaluated for higher doping levels, resulting in increasingly Ohmic behaviour. This is attributed to an enhancement of tunneling through a thinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…It is well-known that an energy barrier for holes transport is generated between the front ZnO electrode and p-layer, which deteriorates the performance of a-Si:H solar cells [37,38]. To solve this problem, a front contact layer with high conductivity to enable tunneling transport of holes is inserted between the front TCO and the p-layer.…”
Section: P-sio X As Contact Layer For High V Oc A-si:h Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that an energy barrier for holes transport is generated between the front ZnO electrode and p-layer, which deteriorates the performance of a-Si:H solar cells [37,38]. To solve this problem, a front contact layer with high conductivity to enable tunneling transport of holes is inserted between the front TCO and the p-layer.…”
Section: P-sio X As Contact Layer For High V Oc A-si:h Solar Cellsmentioning
confidence: 99%
“…To solve this problem, a front contact layer with high conductivity to enable tunneling transport of holes is inserted between the front TCO and the p-layer. The p-doped nc-Si:H, nc-SiC:H and nc-SiO x layers have been demonstrated to be suitable for contact layer [37][38][39][40]. A wide bandgap of the contact layer is also favorable to reduce the optical absorption loss in the short wavelength region.…”
Section: P-sio X As Contact Layer For High V Oc A-si:h Solar Cellsmentioning
confidence: 99%
“…Based on an effective mass of 0.16, we obtain a theoretical Richardson’s constant of 19.2 (Supporting Information D) and note that an error of 2 in A* results in an error of only 0.7 kT / q in Φ B . From Figure (a), it is observed that the I – V characteristics plotted on a log–linear scale have significant nonlinearity, resulting in a temperature dependent ideality factor between 6–12 that we report here for the first time in this type of contact to a 2DHG in GaN. Figure (a) also shows a hypothetical curve with n = 1, whereas n > 1 is evidenced by the flattening of the I – V characteristic . Near to 0 V, there is little change of current with voltage; hence, n = 6–12 reflects the variation only due to T , in the term ( nkT ) in eq .…”
mentioning
confidence: 75%
“…Electrons can cross it without an energy barrier. However, in a p‐i‐n structure, the HTL having a large valence band maximum is directly contacted with the n‐type TCO, which may create an energy band misalignment and therefore deteriorate the photovoltage output and the fill factor (FF) …”
Section: Characteristics Of the Pscs With Different Thickness Of Ni Lmentioning
confidence: 99%